Shelf ecosystems along the U.S. Atlantic Coastal Plain prior to and during the Paleocene-Eocene Thermal Maximum - Doubrawa, Monika; Stassen, Peter; Robinson, Marci M; Babila, Tali L; Zachos, James C; Speijer, Robert P (PANGAEA, 2022)
The Paleocene-Eocene Thermal Maximum (PETM) is the most pronounced climate event of the early Paleogene. It is characterized by negative δ18O and δ13C excursions recorded in sedimentary archives and a transient disruption of the marine biosphere. Bulk carbonate and foraminiferal δ13C records from Paleocene-Eocene core sections from the U.S. Atlantic Coastal Plain show an additional small, but distinct δ13C excursion below the onset of the PETM, coined the “pre-onset excursion” (POE). This study focuses on the South Dover Bridge (SDB) core in Maryland, where the Paleocene-Eocene transition is stratigraphically constrained by calcareous nannoplankton and stable isotope data, and in which the POE is well-expressed. The site was situated in a shallow marine shelf setting near a major outflow of the paleo-Potomac River system (38°44′49″N latitude, 76°00′25″W longitude, Talbot County). We generated high-resolution benthic foraminiferal assemblage, stable isotope, trace-metal, grain size and clay mineralogy data. Data collection was done via core-sampling, and successive preparation of the samples according to each proxy. Foraminifera underwent wet sieving (>63 μm), picking and mounting on Plummer slides. For geochemistry analysis Cibicidoides alleni (Paleocene) and Anomalinoides acutus (PETM) were used. Grain size data was collected with a Laser Diffraction Particle Analyzer. Stable isotope samples were analyzed with a Kiel Mat 253 gas source mass spectrometer system. All carbon isotope values are given in δ13C notation, relative to the PeeDee belemnite Standard (PDB). Trace elemental analyses were carried out on a Thermo Scientific Element XR Sector Field Inductively Coupled Plasma Mass Spectrometer (SF-ICP-MS). For clay mineral analysis, after Jackson treatment, a Philips PW 1380 diffractometer equipped with CuKalpha radiation, 45kV and 30mA graphite monochromator and was quantified through Rietveld Refinement for clay content.
Keywords: Benthic foraminifera; CaCO3 content; grainsize; kaolinite; Maryland; Mg/Ca; Mg/Ca paleothermometry; Paleocene; Paleocene-Eocene Thermal Maximum; PETM; POE; Pre-onset excursion; South Dover Bridge; Stable isotope; Taxonomy; U.S. Atlantic Coastal Plains